Management of the adverse effects of immune checkpoint therapy - Bošnjak, Snežana (Archives of Pharmacy, 2022)
Today immunotherapy with immune checkpoint inhibitors such as a-CTLA4, a-PD-1, and a-PD-L1 antibodies is standard for the treatment of many solid tumors and haematological malignancies. Side effects of these drugs can be general, non-specific (weakness, infusion-related reactions) or specific, so-called immune-related adverse effects (irAEs). Specific side effects are results of the mechanism of action of these drugs, which is non-specific activation of immune system. Clinically, they manifest as organ and tissue inflammation. Almost all organ and system can be affected by irAEs, although side effects on the gastrointestinal tract, skin, liver, endocrine glands and lungs are the most common. The side effects of checkpoint inhibitors are usually transient and mild, but can be also serious or even fatal. The lecture will present general principles for early identification, evaluation and control of irAEs, recommendations from published clinical practice guides, authors' previous clinical experience and open questions that still pose a challenge in clinical practice.